2010
DOI: 10.1175/2010jcli3514.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution and Characteristics of Diurnally Varying Low-Level Jets

Abstract: This study documents the global distribution and characteristics of diurnally varying low-level jets (LLJs), including their horizontal, vertical, and temporal structure, with a special emphasis on highlighting the underlying commonalities and unique qualities of the various nocturnal jets. Two tools are developed to accomplish this goal. The first is a 21-yr global reanalysis performed with the fifth-generation Pennsylvania State University-NCAR Mesoscale Model (MM5) using a horizontal grid spacing of 40 km. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
171
3
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(197 citation statements)
references
References 71 publications
8
171
3
15
Order By: Relevance
“…They investigate the persistent katabatic flows over the coasts Greenland and found the strongest wind speeds over eastern, northern and western coasts of Greenland at the lowest model level, which agrees well with our results in Figure 2(a) and (c) that show almost persistent, shallow katabatic LLJs over the same areas. Rife et al (2010) studied nocturnal LLJs globally and found larger values of their LLJ index around and over southern parts of Greenland during January compared to July. Their results suggest that increased LLJ occurrence in the North Atlantic and southern parts of Greenland is due to enhanced synoptic activity during the winter months.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…They investigate the persistent katabatic flows over the coasts Greenland and found the strongest wind speeds over eastern, northern and western coasts of Greenland at the lowest model level, which agrees well with our results in Figure 2(a) and (c) that show almost persistent, shallow katabatic LLJs over the same areas. Rife et al (2010) studied nocturnal LLJs globally and found larger values of their LLJ index around and over southern parts of Greenland during January compared to July. Their results suggest that increased LLJ occurrence in the North Atlantic and southern parts of Greenland is due to enhanced synoptic activity during the winter months.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…), while there are usually minima in wind speed 1.0 to 2.0 km above the core (Rife et al, 2010). A diurnal cycle is a common and well-documented feature of the NLLJ, with onset and cessation times generally in the early evening and midmorning, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Synoptic cold fronts are known to lead to strong surface winds, resulting in dust storms over the Taklimakan and Gobi deserts (Sun et al, 2001). Another mechanism that can lead to strong surface winds in semi-arid and desert regions is through the formation of a nocturnal low-level jet (NLLJ) (Fiedler et al, 2013;Rife et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of the GPLLJ region using simulations by GCMs (Jiang et al 2007;Cook et al 2008) and RCM and high-resolution regional reanalyses (Rife et al 2010;Wang et al 2010;Cerezo-Mota et al 2011) have been performed. While the detailed study of GPLLJ is not the main objective of the present study, we will use the approaches developed in these studies for the general evaluation of the CRCM5 performance in reproducing the GPLLJ.…”
Section: Introductionmentioning
confidence: 99%